Surviving Sepsis Guideline–Directed Fluid Resuscitation: An Assessment of Practice Patterns and Impact on Patient Outcomes - Austin B. Govero, MD; Siva Naga S. Yarrarapu, MBBS, MD; Michael F. Harrison, MD, PhD; Hassan Z. Baig, MBBS, BMBS; Pramod Guru, MBBS, MD; Pablo Moreno Franco, MD; Sean M. Caples, DO, MS; Ami A. Grek, APRN, DNP; Michael R. Vizzini, MBA, MHA; Colleen T. Ball, MS; Syed A. Khan, MD; Katherine J. Heise, APRN, CNP, MSN; et al. (Critical Care Explorations, 2022)
IMPORTANCE:. Aggressive fluid resuscitation remains a cornerstone of the Surviving Sepsis Campaign (SSC) guidelines, but there is growing controversy regarding the recommended 30 mL/kg IV fluid dosage. It is contended that, in selected patients, this volume confers an increased risk of volume overload without either concomitant benefit or strong evidence in support of the recommended IV fluid dosage. OBJECTIVES:. Assessment of practice patterns and their impact on patient outcomes following the surviving sepsis guidelines for fluid resuscitation. DESIGN:. Large, multisite retrospective cohort study. SETTING AND PARTICIPANTS:. The retrospective study included all adult patients who presented to the emergency department at one of 19 different Mayo Clinic sites throughout the Midwest, Southeast, and Southwest from August 2018 to November 2020 with suspected sepsis. MAIN OUTCOMES AND MEASURES:. Eight-thousand four-hundred fourteen patients suspected to have sepsis were assessed regarding fluid resuscitation and outcomes among patients receiving 30 mL/kg IV fluid dosing compared with patients who did not. Patient demographics and clinical information were collected via electronic health records. Patients were divided into two cohorts: those who received 0–29.9 mL/kg of IV fluid and those who received 30.0+ mL/kg of IV fluid. Statistical analyses were performed to evaluate the impact of fluid dose on in-hospital death, 30-day mortality, ICU admission after diagnosis, dialysis initiation after diagnosis, ventilator use, vasopressor use, as well as ICU and hospital length of stay. RESULTS:. We observed lower in-hospital mortality and 30-day mortality risk in the 30+ mL/kg dosing group. Increased fluid dosage did, however, carry a much greater chance of ICU admission. Most patients (72% after propensity score weighting) in our population received less than 30 mL/kg fluid (based on ideal body weight). CONCLUSIONS AND RELEVANCE:. IV fluid dosing for sepsis resuscitation greater than 30 mL/kg was associated with decreased risk of in-hospital mortality, 30-day mortality, and reduced risk of requiring mechanical ventilation. Our data does ultimately seem to support the SSC recommendation.